IMPLEMENTATION D’UNE APPLICATION INFORMATIQUE DISTRIBUEE POUR LA FACTURATION DES ABONNES DE LA REGIDESO / KISANGANI - MAVUETA, Vigeol MAVUNGU (IJRDO -Journal of Computer Science Engineering, 2022)
The implementation of a distributed computer application is the current trend of software development teams in companies. However, there are a lot of problems in its realization due to the multiple technologies that are involved in its implementation. In this article, we review the essential steps in the construction of a distributed application based on adapted software architectures. This is the case of the company Regideso / Kisangani which, in the need to maximize its revenues in its billing process of its subscribers, does not have an appropriate and efficient tool for collecting water consumption data from its subscribers. The objective of this paper is to define the analytical and conceptual steps of a distributed computing application based on server-side REST technology consumed by a mobile application under Android allowing this company to have a system adapted to its needs and which is directly linked to the rest of its IT infrastructure.